“The Beginning of the End”. The Lofts of SoHo and the Role of Artists in the Early Days of Gentrification in New York City (KULT_online, 2017)
Aaron Shkuda’s The Lofts of SoHo recounts how between 1950 and 1980 the New York City neighborhood of SoHo turned from an inner-city industrial district into an artist’s enclave, thereby laying the groundwork for the gentrified space that SoHo represents today. Shkuda’s account focuses on the role that artists played in transforming the neighborhood and analyzes how artists entangled with other political and economic actors were crucial in the redevelopment of the neighborhood after and during its deindustrialization. By analyzing the 20th-century redevelopment and eventual gentrification of SoHo in extraordinary detail and structural clarity, the book makes a very valuable contribution to the study of gentrification in New York City and US-American cities that – although historical in scope – is of pressing interest for students of today’s city as well.